The ideological fragmentation of Indonesian Muslim students and da’wa movements in the postreformed era - Abdul Basit (IAIN Salatiga, 2016)
The presence of post-reformation religious organizations has influenced students’ ideology and movements. Thus, this study explains the processes of Muslim students’ ideological fragmentation and its implications to the future of students’ post-reformation movements. This study is conducted through observations and interviews to extracurricular organizational activists in Purwokerto. Reflective analysis is then conducted using primary and secondary data. Islamic ideology has many important roles, such as guidance, values, beliefs, and directions for da’wa (Islamic missionary)activities. In its operation, Islamic ideology is fragmented into fundamental, modernist, liberal, and traditional ideology. The ideological processes are influenced by several factors, such as organization historical background, ideological relationship with social organizations, development of Islamic transnational organizations, students’ increasing demands and needs in modern era, as well as the presence of massive information media. The Implications of ideological fragmentation influence post-reformation activities performed by those Muslim students. They donot only perform religious activities by mentoring as previously performed in the new order, but also doing debate activities onIslamic theology, politics, community empowerment, global awareness,issues on humanities, and responses to the development of science and technology.The presence of ideological fragmentation may not be negatively faced andconsolidated in a single view. The most important one is how to critically and constructively maintain and develop the ideology. Munculnya berbagai organisasi keagamaan pasca reformasi memiliki dampak pada ideologi dan gerakan mahasiswa. Oleh karena itu, pada tulisan ini akan diuraikan tentang proses terjadinya fragmentasi ideologi pada mahasiswa muslim dan implikasinya terhadap masa depan gerakan mahasiswa muslim pasca reformasi. Kajian dilakukan dengan cara observasi dan wawancara dengan para aktivis organisasi ekstra kampus di Purwokerto. Kemudian, penulis melakukan analisis-reflektif dengan menggunakan data-data dari sumber utama dan data pustaka. Ideologi Islam memiliki peranan yang amat penting sebagai pedoman, nilai, keyakinan dan arah untuk menggerakkan kegiatan-kegiatan dakwah. Ideologi tersebut dalam operasionalisasinya terjadi fragmentasi yang mengarah pada fundamental, modernis, liberal, dan tradisional. Proses terjadinya ideologi dipengaruhi oleh beberapa faktor di antaranya: latar belakang sejarah organisasi, memiliki hubungan ideologis dengan organisasi kemasyarakatan, berkembangnya organisasi-organisasi Islam transnasional, tuntutan dan kebutuhan mahasiswa era modern, serta adanya media informasi yang semakin massif. Implikasi dari fragmentasi ideologi Islam berdampak pada ragamnya kegiatan-kegiatan yang dilakukan oleh mahasiswa muslim pasca reformasi. Mereka tidak hanya melakukan kegiatan keagamaan melalui mentoring saja seperti yang terjadi pada era Orde Baru, melainkan juga menghadirkan kegiatan-kegiatan yang mengarah pada perdebatan teologi Islam, politik mahasiswa,pemberdayaan masyarakat, kepedulian pada masalahmasalah kemanusiaan dan global, serta responsif terhadap perkembangan ilmu dan teknologi.Adanya fragmentasi ideologi tidak perlu disikapi secara negatif dan tidak bisa disatukan dalam satu warna. Tugas kita adalah bagaimana memelihara dan mengembangkan ideologi tersebut secara kritis-konstruktif